Adipose tissue dysfunction and hypertriglyceridemia: mechanisms and management - van de Woestijne, A. P; Monajemi, H; Kalkhoven, E; Visseren, F. L. J (Obesity reviews, 2011)
Elevated plasma triglyceride levels, as often seen in obese subjects, are independently associated with an increased risk of cardiovascular diseases. By secreting adipokines (such as adiponectin and leptin) and other proteins (such as lipoprotein lipase and cholesteryl ester transferase protein), adipose tissue affects triglyceride metabolism. In obesity, adipocyte hypertrophy leads to many changes in adipocyte function and production of anti‐ and pro‐inflammatory cytokines. Furthermore, free fatty acids are released into the circulation contributing to insulin resistance. Adipose tissue dysfunction will eventually lead to abnormalities in lipid metabolism, such as hypertriglyceridemia (due to increased hepatic very‐low‐density lipoprotein production and decreased triglyceride hydrolysis), small dense low‐density lipoprotein particles, remnant lipoproteins and low high‐density lipoprotein cholesterol levels, all associated with a higher risk for the development of cardiovascular diseases. The clinical implications of elevated plasma triglycerides are still a matter of debate. Understanding the pathophysiology of adipose tissue dysfunction in obesity, which is becoming a pandemic condition, is essential for designing appropriate therapeutic interventions. Lifestyle changes are important to improve adipose tissue function in obese patients. Pharmacological interventions to improve adipose tissue function need further evaluation. Although statins are not very potent in reducing plasma triglycerides, they remain the mainstay of therapy for cardiovascular risk reduction in high‐risk patients.